THE ENGLISH LEARNING STYLES ON THE SECOND SEMESTER ENGLISH EDUCATION STUDENTS’ OF BATANGHARI UNIVERSITY IN ACADEMIC YEAR 2014/2015 - Kartika Dewi (Universitas Batanghari Jambi, 2015)
In this research study, the researcher to investigate the students learning style on the second Semester English Education Students’ of Batanghari University In Academic Year 2014/2015. The method was used n this research was descriptive qualitative. The sample consisted of 61 students. The instrument by applying random sampling technique. The data of this research was collected from observations, and questionnaire. The data questionnaire used analyzed by using SPPS 20.00. It was used to analyzing the question base on the category of students learning style. The Second Semester English Education Students’ of Batanghari University. Base on the category of students learning style, the students who had the Auditory are 49 students and it is the high score 37 % and the medium score visual style with 37 students with percentage score 47%. The last is Kinesthetic style are 13 students with percentage 4%. In conclusion learning styles on the second semester English education students of Batanghari University in Academic year 2014-2015 dominated is auditory styleKey Words: Learning Styles, Visual, Auditory, Kinesthetic